Transformational Leadership and Servant Leadership dalam Perspektif Islam - Kurnia, Neneng (Indra Institute Research & Publication, 2026)
This study examines two leadership models transformational leadership and servant leadership from an Islamic perspective. The issue addressed concerns how these two leadership models can be applied within Islamic organizational contexts and how they differ in achieving shared organizational goals. The purpose of this study is to analyze the principles of transformational leadership and servant leadership within the framework of Islamic teachings and to explore how both models contribute to the effectiveness of organizations grounded in Islamic values. The research employs a qualitative literature review method, analyzing texts related to Islamic leadership as well as contemporary leadership studies published between 2015 and 2025. The findings indicate that transformational leadership in Islam emphasizes personal transformation through spiritual and moral development, characterized by four core dimensions: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. In contrast, servant leadership prioritizes service, empathy, and self-sacrifice for the collective good by placing followers’ needs at the forefront. Recent empirical studies demonstrate that both leadership models have been successfully implemented in Islamic educational institutions. Transformational leadership shows a significant positive effect on organizational commitment (r = 0.68, p < 0.01), while servant leadership exhibits a strong association with job satisfaction (β = 0.72, p < 0.001). Although differing in focus, these two approaches complement one another in fostering effective leadership rooted in Islamic values such as trustworthiness (amanah), justice (‘adl), and consultation (shura). The study concludes that both leadership models are relevant for enhancing leadership quality in Islamic organizations. The synergy between transformational and servant leadership forms an inclusive Islamic leadership model that balances organizational change with human-centered service. The implications suggest that applying both models can strengthen leadership values oriented toward service and positive social transformation, particularly within Islamic educational institutions facing contemporary challenges in the digital era.